The Potential of Video Media in Enhancing the Effectiveness of Islamic Education Learning in the Digital Era - Rabiatul Ismi; Hafifatun Natasya; Maulana Fathur Rizqia; Vika Yuniar; Safar Wardana; Abdul Azis (The Future of Education Journal, 2026)
This study aims to examine the potential of video media in improving the effectiveness of Islamic Religious Education (PAI) learning in the digital era. This research employed a qualitative descriptive approach using library research methods. Data were collected from scientific journals, books, and relevant research articles related to the use of video media in PAI learning. The findings indicate that video media has significant potential in enhancing students’ learning motivation, improving understanding of abstract materials, strengthening memory retention, and supporting the development of Islamic moral values and character. Through audio-visual presentations, video media creates more interactive, interesting, and contextual learning experiences. In addition, video-based learning supports independent learning because students can access learning materials repeatedly through digital devices. However, the implementation of video media in PAI learning still faces several challenges, including limited technological facilities, internet accessibility, and teachers’ competence in selecting and developing appropriate learning videos. Therefore, video media can serve as an effective innovation to improve the quality of Islamic Religious Education learning in the era of information technology.